Pendampingan Literasi Keuangan Tentang Pentingnya Berinvestasi Di Kelurahan Ponjalae, Kota Palopo - Risnawati Ramli (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Based on the situation analysis obtained from the literature review and visits to partner locations, various problems were found in kelurahan Ponjalae so that community service activities were in accordance with the needs of the partner community. The implementation of community service activities aims to increase understanding of the importance of investment. The seminar method is used as the main approach in this intervention. Financial literacy assistance activities are integrated into a series of comprehensive seminar sessions, including the delivery of basic and practical theories, then continued with interactive discussion sessions. Analysis of the effectiveness of this intervention was carried out by evaluating the increase in participant knowledge. The results showed a significant increase in understanding the theoretical and practical concepts of investment. This activity is a solution to the main problems faced by the community in kelurahan Ponjalae. The implications of this study include increasing the economic welfare of the community, strengthening social stability, increasing participation in economic development, increasing awareness of the importance of financial education, and increasing economic productivity.